Pengembangan Konseling Individu Realita Teknik Want, Doing and Direction, dan Planning Untuk Meningkatkan Disiplin Belajar Siswa - I Komang Sri Sudha Hiswana; Ni Ketut Suarni; Gede Nugraha Sudarsana (Universitas Pendidikan Ganesha, 2022)
This study is a development research. The product developed is a Reality Individual Counseling Guide Using the WDEP Technique to Improve Student Discipline. The development procedure in this study uses the 4D development model proposed by Thiagarajan as follows: (1) Defining Stages (Define), (2) Design Stages, (3) Development Stages (Develop), (4) Deployment Stages (Development Stages). disseminate). The subjects involved in this study were 5 experts in counseling guidance, including 3 Counseling Guidance lecturers at FIP ​​Undiksha and 2 Counseling Guidance Teachers at SMP Negeri 1 Sukasada. Based on expert calculations, the CVR (content validity ratio) got a result of 21.2. Furthermore, calculating the value of CVI (Content Validity Index) based on the calculation of expert judgment, obtained a CVI of 0.96, this value is included in the Very Appropriate category. Furthermore, in order to test the effectiveness of the individual counseling guidebook, the reviewer involved 5 students as the subject of the study. Hypothesis testing shows that the Development of Reality Individual Counseling Guidebooks with WDEP Techniques is Effective to improve Learning Discipline with a t-count of 8.525 with a significance level of 0.05 and a score of ES = 3.81 which belongs to the Very Large ES category. Abstrak: Kajian ini merupakan penelitian pengembangan. Produk yang dikembangkan ialah Buku Panduan Konseling Individu Realita Dengan Teknik WDEP Untuk Meningkatkan Disiplin Belajar Siswa. Prosedur pengembangan dalam penelitian ini menggunakan model pengembangan 4D yang dikemukakan oleh Thiagarajan yaitu sebagai berikut : (1) Tahapan Pendefinisian (Define), (2) Tahapan Perancangan (Design), (3) Tahapan Pengembangan (Develop), (4) Tahapan Penyebaran (Disseminate). Subjek yang terlibat pada kajian ini yakni 5 orang ahli dalam bimbingan konseling, diantaranya 3 orang dosen Bimbingan Konseling FIP Undiksha serta 2 orang Guru Bimbingan Konseling SMP Negeri 1 Sukasada. Berdasarkan perhitungan pakar didapatkan CVR (content validity ratio) mendapatkan hasil 21,2. Selanjutnya menghitung nilai CVI (Content Validity Index) berdasarkan perhitungan penilaian pakar didapatkan CVI sebesar 0,96 , nilai ini termasuk kedalam kategori Sangat Sesuai. Selanjutnya dilakukan Guna menguji efektivitas buku panduan konseling individu, pengkaji melibatkan 5 siswa sebagai subjek kajian. Pengujian hipotesis menunjukan bahwasanya Pengembangan Buku Panduan Konseling Individu Realita Dengan Teknik WDEP Efektif guna meningkatkan Disiplin Belajar dengan t-hitung 8,525 dengan taraf signifikansi 0,05 serta skor ES = 3,81 yang tergolong dalam kategori ES Sangat Besar